A Semi-Analytical Model of Cyclic Behavior of Reinforced Concrete Joints Rehabilitated with FRP. Issue 12 (December 2013) - Mukherjee, Abhijit; Jain, Kamal Kant
This paper presents a semi-analytical model for damaged reinforced concrete (RC) beam-column joints that are restored with fiber reinforced polymers (FRP). Constituent materials are characterized by their stress-strain curves. Confinement to concrete offered by the FRP is discussed. Stress-strain behavior of control and yielded steel bars and FRP laminate are presented. Material properties are utilized to develop the cross-sectional model in the form of moment-curvature ( M -φ) relationships. Effect of confinement and longitudinal FRP reinforcement on moment-curvature relationships is discussed. Cross sectional properties are extended to obtain the load-displacement relationships of the beam-column joints. A softening model is developed to incorporate the progressive damage of the joint. Variations of softening coefficient with displacement cycles, displacement history and confinement are reported. Models presented are validated using experimental results.